“Con las lagañas de un perro puedes ver a los muertos”. Representaciones plásticas y verbales de los perros en la comunidad purépecha de Ocumicho - Eva María Garrido Izaguirre (Nuevo mundo - Mundos Nuevos, 2021)
The article focuses on the analysis of the representations of dogs that appear in the daily, mythical, historical and aesthetic life of Ocumicho, a community belonging to the Purépecha ethnic group in Mexico. The polychrome clay sculptures, made by the women of the town, find meaning in the multiple stories that link the dog with the devil and the underworld. Dogs are ambivalent, they articulate different worlds, they are signs of bad omen and companion animals that ensure the transit after death. Dogs are hinges between the world of the living and that of the dead, just as they were in Mesoamerican cultures. The relationship between dog, death, and the devil is anchored in the parallels woven between the Mesoamerican underworld and the European hell. In contemporary Ocumicho the qualities of the dog are enriched by integrating into the relational complex of representations of the devil, his spaces, his agents and interlocutors.